The trends of blood culture contamination and utilization rates in an LMIC tertiary care center from 2010 to 2022: a call for diagnostic stewardship? - Lama Saleh; Amanda Chamieh; Rima El Basst; Eid Azar (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract